Managing Human Capital Through the Use of Performance Improvement Plans - Costakis, Helena R.; Pickern, Jay S. (Journal of Applied Business and Economics, 2022)
Management of human capital through the use of performance management systems and performance improvement plans is of the utmost importance to managers. Employees are the most valuable assets companies possess. Effective management of human capital can have a direct impact on individual and team performance, as well as the success of the business. This paper focuses on the use of the performance improvement plan and its impact on employee performance outside of the progressive disciplinary process. In this paper, we review the existing literature on human capital and performance improvement plans, and make managerial recommendations for the use of performance improvement plans going forward.